Criteria for matching fragmented archaeological textiles: a survey - Gigilashvili, Davit; Lukesova, Hana; Hardeberg, Jon Yngve (Archaeological Textiles Review, 2024)
Archaeological textiles are a valuable source for understanding past cultures. However, textiles are vulnerable to decomposition and often found in a fragmentary state. Textile experts rely on their eyes and experience for manually matching similar fragments to reconstruct the original item. This requires much time and effort, as well as physical interaction with fragile artifacts. Computer-assisted virtual reconstruction has been recently proposed. Computer scientists suggested that the algorithms could mimic the criteria used by human experts. These criteria are rarely obvious or well-documented. To facilitate future interdisciplinary research efforts, a survey among archaeologists and conservators was conducted. This work explores what criteria are used by experts for matching fragments in the reconstruction process, which in turn may inspire the development of computational algorithms. Furthermore, the study evaluates the awareness among archaeologists and conservators of existing opportunities for computer-assisted reconstruction, their technological requirements and overall openness to such novel interdisciplinary solutions.